2021
DOI: 10.1155/2021/9939403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Isoflavonoid Biosynthesis-Related R2R3-MYB Transcription Factors in Callerya speciosa (Champ. ex Benth.) Schot Using Transcriptome-Based Gene Coexpression Analysis

Abstract: The R2R3-MYB family is one of the largest plant transcription factor (TF) families playing vital roles in defense, plant growth, and secondary metabolism biosynthesis. Although this gene family has been studied in many species, isoflavonoid biosynthesis-related R2R3-MYB TFs in Callerya speciosa (Champ. ex Benth.) Schot, a traditional Chinese medicinal herb, are poorly understood. Here, a total of 101 R2R3-MYB TFs were identified from C. speciosa transcriptome dataset. 25 clades divided into five functional gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…p -Coumaroyl-CoA, a key intermediate in the flavonoid biosynthesis pathway, provides the C6–C3–C6 carbon skeleton to the flavonoid compounds ( Yu et al., 2021 ). After the production of p -coumaroyl-CoA, the biosynthetic pathway of flavonoids begins to branch under the activity of CHS, CHR, and CHI ( Wang et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…p -Coumaroyl-CoA, a key intermediate in the flavonoid biosynthesis pathway, provides the C6–C3–C6 carbon skeleton to the flavonoid compounds ( Yu et al., 2021 ). After the production of p -coumaroyl-CoA, the biosynthetic pathway of flavonoids begins to branch under the activity of CHS, CHR, and CHI ( Wang et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under ABA treatment, the ideal reference genes of Nitraria tangutorum were EF1-α and His [20]. Our previous studies revealed that several R2R3-MYB TFs and structural genes might be involved regulating iso avonoid biosynthesis in C. speciosa, and CsMYB36 has the highest expression in R2R3-MYB TFs [21]. To understand these related gene expression changes will be facilitated to explain their functions in C. speciosa under different experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies revealed that several R2R3-MYB TFs and structural genes might be involved regulating isoflavonoid biosynthesis in C. speciosa, in which one of the R2R3-MYB TFs CsMYB36 has a high expression level. 24 Understanding the expression patterns of these genes involved in the pathway of isoflavonoid biosynthesis will be facilitated to understand the accumulation and dynamic trends of (iso)flavonoids in C. speciosa. Furthermore, explaining the molecular mechanism associated with hormone stimuli to exogenous regulators may also help us to reveal what facilitates the quality of C. speciosa.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that flavonoids are synthesized in plants via the phenylpropanoid and acetate–malonate metabolic pathways [ 5 ]. Many flavonoid biosynthesis-related genes have been studied in depth, including those encoding phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumaroyl CoA ligase (4CL) and MYB transcription factors [ 6 ]. In addition, flavonoids can negatively regulate auxin transport [ 7 ].…”
Section: Introductionmentioning
confidence: 99%